Intracranial Extension of Spinal Subarachnoid Hematoma Causing Severe Cerebral Vasospasm - Nam, Kyoung Hyup (J Korean Neurosurg Soc, 2014)
Spinal subarachnoid hemorrhages (SAH) can extend into the intracranial subarachnoid space, but, severe cerebral vasospasm is rare complication of the extension of intracranial SAH from a spinal subarachnoid hematoma. A 67-year-old woman started anticoagulant therapy for unstable angina. The next day, she developed severe back pain and paraplegia. MRI showed intradural and extramedullar low signal intensity at the T2-3, consistent with intradural hematoma. High signal intensity was also noted in the spinal cord from C5 to T4. We removed subarachnoid hematoma compressing the spinal cord. The following day, the patient complained of severe headache. Brain CT revealed SAH around both parietal lobes. Three days later, her consciousness decreased and left hemiplegia also developed. Brain MRI demonstrated multiple cerebral infarctions, mainly in the right posterior cerebral artery territory, left parietal lobe and right watershed area. Conventional cerebral angiography confirmed diffuse severe vasospasm of the cerebral arteries. After intensive care for a month, the patient was transferred to the rehabilitation department. After 6 months, neurologic deterioration improved partially. We speculate that surgeons should anticipate possible delayed neurological complications due to cerebral vasospasm if intracranial SAH is detected after spinal subarachnoid hematoma.